Neural Systems for Own-body Processing Align with Gender Identity Rather Than Birth-assigned Sex. (9th December 2019) - Majid, D S Adnan; Burke, Sarah M; Manzouri, Amirhossein; Moody, Teena D; Dhejne, Cecilia; Feusner, Jamie D; Savic, Ivanka
Abstract: Gender identity is a core aspect of self-identity and is usually congruent with birth-assigned sex and own body sex-perception. The neuronal circuits underlying gender identity are unknown, but greater awareness of transgenderism has sparked interest in studying these circuits. We did this by comparing brain activation and connectivity in transgender individuals (for whom gender identity and birth-assigned sex are incongruent) with that in cisgender controls (for whom they are congruent) when performing a body self-identification task during functional magnetic resonance imaging. Thirty transgender and 30 cisgender participants viewed images of their own bodies and bodies morphed in sex toward or opposite to birth-assigned sex, rating each image to the degree they identified with it. While controls identified with images of themselves, transgender individuals identified with images morphed "opposite" to their birth-assigned sex. After covarying out the effect of self-similarity ratings, both groups activated similar self- and body-processing systems when viewing bodies that aligned with their gender identity rather than birth-assigned sex. Additionally, transgender participants had greater limbic involvement when viewing ambiguous, androgynous images of themselves morphed toward their gender identity. These results shed light on underlying self-processing networks specific to gender identity and uncover additional involvement of emotional processing in transgender individuals.